2022
DOI: 10.3390/ijms232314776
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism ‘Hub’ Gene Expression Associates with Increased Inflammation and Severe Disease Outcomes in COVID-19 Infection and Inflammatory Bowel Disease

Abstract: The epithelial barrier’s primary role is to protect against entry of foreign and pathogenic elements. Both COVID-19 and Inflammatory Bowel Disease (IBD) show commonalities in symptoms and treatment with sensitization of the epithelial barrier inviting an immune response. In this study we use a multi-omics strategy to identify a common signature of immune disease that may be able to predict for more severe patient outcomes. Global proteomic approaches were applied to transcriptome and proteome. Further semi- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…These same metabolic genes are also significantly upregulated in enteric neural cells from CPI colitis versus HC ( figure 4C ). While these pathways have been implicated in UC pathogenesis, 12 13 they also distinctly characterize stromal cells in CPI colitis. Most DE genes between CPI colitis versus HC are distinct from genes from UC comparisons to healthy ( figure 4D,E , left), and in direct comparisons between UC and CPI colitis, NAD + catabolism, tryptophan metabolism, and metallothionein genes are again uniquely upregulated in CPI colitis stroma ( figure 4E , right).…”
Section: Resultsmentioning
confidence: 99%
“…These same metabolic genes are also significantly upregulated in enteric neural cells from CPI colitis versus HC ( figure 4C ). While these pathways have been implicated in UC pathogenesis, 12 13 they also distinctly characterize stromal cells in CPI colitis. Most DE genes between CPI colitis versus HC are distinct from genes from UC comparisons to healthy ( figure 4D,E , left), and in direct comparisons between UC and CPI colitis, NAD + catabolism, tryptophan metabolism, and metallothionein genes are again uniquely upregulated in CPI colitis stroma ( figure 4E , right).…”
Section: Resultsmentioning
confidence: 99%
“…KYNU is widely expressed in nearly all organs of the body, with particularly elevated levels observed in the liver, urinary bladder, and appendix. 50 KYNU is involved in various inflammatory skin diseases, [51][52][53][54][55] cardiovascular diseases, 56 inflammatory bowel disease, 57,58 and several types of cancers, [59][60][61][62][63] exerting its effects through diverse pathways. While previous studies have indicated abnormalities in tryptophan metabolism within HS lesions, 18 there is currently a scarcity of research confirming the distinctive expression pattern of KYNU specifically in HS.…”
Section: Discussionmentioning
confidence: 99%
“…MSD parameters and MRM transitions used for individual metabolites and labelled metabolites were set as previously described. 27…”
Section: Methodsmentioning
confidence: 99%
“…LC-MS/MS analysis of TRP, KYN, 3HK, 3HAA, 5-hydroxytryptophan (5HTP), xanthurenic acid (XA), 5-hydroxyindoleacetic acid (5HIAA), serotonin, KYNA and AA was carried out using a TSQ Vantage mass spectrometer (Thermofisher, USA) connected to a Vanquish solvent delivery/autosampler system (Thermo-Dionex, USA), according to a protocol previously described. 27 Briefly, chromatographic separation was achieved by injecting standards and samples (20 μL) onto a Luna ® PFP(2)100 Å reversed phase column (2 × 150 mm, 3 μm; Phenomenex) with the temperature of the column compartment set at room temperature by reverse phase gradient elution at 25°C. A binary solvent gradient was used which consisted of aqueous 0.1% formic acid (A) and methanol (B) at a flow rate of 300 μL/minute.…”
Section: Quantification Of Metabolites By Lc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation